The head of school administrative staff's strategy in improving administrative services at MAN 2 Model Medan - Salwa Nabila Damanik; Budi Budi (Cendikia : Media Jurnal Ilmiah Pendidikan, 2026)
This research aims to determine the strategies implemented by the head of school administration in improving administrative services at Madrasah Aliyah Negeri (MAN) 2 Medan Model and identify the obstacles faced in its implementation. School administration services are an important part that supports the smooth running of the teaching and learning process, so a strategic approach is needed so that these services can run well and not waste time and money. This research uses a qualitative approach with a descriptive research design. Data was obtained through observation, interviews and document collection conducted with the head of administration and school administrative staff. Data analysis techniques are carried out through the stages of data reduction, data presentation, and drawing conclusions. Research shows that the methods used by heads of administrative staff to improve administrative services include structured work planning, clear assignment of tasks to staff, use of technology to manage data, and implementation of regular monitoring and evaluation. Managing student data, correspondence and student services can be more effective with the right strategy.